2015
DOI: 10.1080/10282580.2015.1025626
|View full text |Cite
|
Sign up to set email alerts
|

‘She’s White and She’s Hot, So She Can’t Be Guilty’: Female Criminality, Penal Spectatorship, and White Protectionism

Abstract: Despite mainstream criminology's burgeoning interest in issues of race, class, and gender, very little scholarship has examined whiteness and its attendant privileges in understanding public discourse on criminal offenders. This paper examines the role of penal spectatorship as a discursive mechanism by which white, female offenders are protected in public spaces by virtue of their racial and gender identity. Using a content analysis of comments posted on the mug shot images of white women on a popular 'mug sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…The present study employed qualitative content analysis to examine published personal accounts of currently and formerly incarcerated women in order to deepen our understanding of their experiences in the criminal justice system. Content analysis has been used previously to examine issues related to women and criminal justice, including sexual assault during incarceration (Alarid, 2000), risk and resilience factors among incarcerated mothers (Schlager & Moore, 2014), gender differences in the experience of military imprisonment (Treacy, 1996), and civilian interest in criminal proceedings for entertainment purposes (Dirks, Heldman, & Zack, 2015). However, no empirical studies were found which examined women's experiences of incarceration while also emphasizing the implications for social work practice and criminal justice reform.…”
Section: Methodsmentioning
confidence: 99%
“…The present study employed qualitative content analysis to examine published personal accounts of currently and formerly incarcerated women in order to deepen our understanding of their experiences in the criminal justice system. Content analysis has been used previously to examine issues related to women and criminal justice, including sexual assault during incarceration (Alarid, 2000), risk and resilience factors among incarcerated mothers (Schlager & Moore, 2014), gender differences in the experience of military imprisonment (Treacy, 1996), and civilian interest in criminal proceedings for entertainment purposes (Dirks, Heldman, & Zack, 2015). However, no empirical studies were found which examined women's experiences of incarceration while also emphasizing the implications for social work practice and criminal justice reform.…”
Section: Methodsmentioning
confidence: 99%
“…In response, an emerging body of research has begun to explore how social constructions of crime and related criminal justice responses account for what Eastman (2015) terms "white innocence," or processes that "rationalize, excuse, and overlook White deviance" (239). Some of this research explores how mug shots of White women are viewed with empathy (Dirks, Heldman, and Zack 2015), how White militant radicalization is often associated with aspirations for individualism rather than violence (Wood, Jakubek Jr, and Kelly 2015), and how mass shootings committed by young White men are often attributed to mental health factors rather than a predisposition to violence (Heitzeg 2015). Related research has also found that Whites are overrepresented as victims of crime as well as law enforcement officers in local television news (Dixon 2017).…”
Section: Protection Of White Bodiesmentioning
confidence: 99%
“…Likewise, research reveals a different set of experiences among U.S. White women who experience incarceration compared to their Black counterparts. Dirks, Heldman, and Zack (2015) found that the deviant label for White women did not uphold despite the crimes committed. The authors' examination of penal spectatorship revealed that convicted White women are viewed as victims of circumstance deserving of empathy and redemption rather than criminals.…”
Section: )mentioning
confidence: 99%
“…Thus, "White protectionism" guards them against "deviant" or "criminal" designators. Even the media are found to depict White women offenders as less blameworthy and more capable of reform as compared to non-white women (Dirks, Heldman, & Zack, 2015). What this shows is that the experiences and perceptions of women who have been convicted of a crime changes at the intersection of race, gender, and social class.…”
Section: )mentioning
confidence: 99%